Tilt signals at Mount Melbourne, Antarctica: evidence of a shallow volcanic source - Salvatore Gambino; Angelo Ferro; Marco Aloisi; Giuseppe Falzone (Polar Research, 2016)
Mount Melbourne (74°21′ S, 164°43′ E) is a quiescent volcano located in northern Victoria Land, Antarctica. Tilt signals have been recorded on Mount Melbourne since early 1989 by a permanent shallow borehole tiltmeter network comprising five stations. An overall picture of tilt, air and permafrost temperatures over 15 years of continuous recording data is reported. We focused our observations on long-term tilt trends that at the end of 1997 showed coherent changes at the three highest altitude stations, suggesting the presence of a ground deformation source whose effects are restricted to the summit area of Mount Melbourne. We inverted these data using a finite spherical body source, thereby obtaining a shallow deflation volume source located under the summit area. The ground deformation observed corroborates the hypothesis that the volcanic edifice of Mount Melbourne is active and should be monitored multidisciplinarily. Keywords: Tilt monitoring; volcanic dynamics; physics volcanology; ground deformation; Victoria Land. (Published: 1 June 2016) To access the supplementary material for this article, please see the supplementary files in the column to the right (under Article Tools). Citation: Polar Research 2016, 35 , 28269, http://dx.doi.org/10.3402/polar.v35.28269